Tropical Cyclones. Issue 3 (8th August 2022) - Lin, Jialin; Qian, Taotao; Klotzbach, Philip
Abstract: This paper reviews the history of tropical cyclone research from the late nineteenth century until the present with an emphasis on observational studies. The topics include tropical cyclone theory, climatology, structure, genesis indices and intraseasonal-to-centennial variability and trends. Possible future directions are also suggested.